Reading Habits, Interests, And Reading Comprehension Of Students In Schools Implementing School Literacy Movement - Ulfa Khaira; Mohammad Harun; Rajab Bahry (Universitas Negeri Makassar, 2019)
This research aims to describe the reading habits, interests, and reading comprehension of grade X students at high schools implementing the School Literacy Movement (GLS) program in Banda Aceh and Aceh Besar, Aceh. The research method used was descriptive method with a quantitative approach. The sample was 114 grade X students of SMAN 2 Banda Aceh, Unsyiah Laboratory High School, MAS Ruhul Islam Anak Bangsa, and MAS Insan Qurani. This research used a questionnaire and tests as research instruments. Data analyzed by a descriptive qualitative technique by listing raw scores, calculating the average student score, and classifying the results of the samples studied. Research result indicated that the level of reading habits, interests, and reading comprehension of X grade students at high schools implementing the School Literacy Movement program (GLS) varied and had not reached the maximum result. First and foremost, the average mark of reading habits obtained by the four schools is 61% (moderate category) and the average mark of X grade students’ reading habits in each school was also in the moderate category: 59% in SMAN 2 Banda Aceh, 58% in Unsyiah Laboratory High School, 63% in MAS RIAB, and 65% in MAS Insan Qurani. Second, the level of students’ reading interest in those four schools was 67% (moderate category), while the average mark of students’ reading interest in each school was categorized moderate and good, 65% in SMAN 2 Banda Aceh, 62% in Unsyiah Laboratory High School, 71% in MAS RIAB, and 71% in MAS Insan Qurani. Last, reading comprehension level in these four schools was 61% (moderate category), while the average mark for reading comprehension of X grade students in each school was categorized moderate and good, 40% in SMAN 2 Banda Aceh, 65% in Unsyiah Laboratory High School, 71% in MAS RIAB, and 69% in MAS Insan Qurani.